THE USE OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) METHOD TO IMPROVE WRITING ABILITY OF THE SECOND YEAR STUDENTS OF MTS AL FAJAR PEKANBARU - Mila Dwi Astuti; Eliwarti Eliwarti; Novitri Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aimed to find out whether the use of CIRC method could improve the writing ability of the second year students of MTs Al Fajar Pekanbaru. This research used classroom action research design and collected the data by using test and observsation sheets. Test used to measure the students’ progress in every cycle during the classroom action research. This test consisted of pre-test and post-test. Observation sheets used to observe the teacher’s and students' activities in the classroom. There were 25 students as participants. The level of achievement in this research was 75, based on the standard minimum criteria of achievement of English subject in MTs Al Fajar Pekanbaru. The research finding showed that the implementation of applying CIRC method as the teaching method could improve students’ writing ability at the first and second cycle. Based on the data analysis, the students’ scores improved from 63,47 in pre-test to 78,61 in post-test. Thus, the implementation of CIRC method could improve students’ writing ability of the second year students of MTs Al Fajar Pekanbaru.Keywords: CIRC Method, Writing Ability, Narrative Text